Neuronal Expression of the Human Neuropeptide S Receptor NPSR1 Identifies NPS-Induced Calcium Signaling Pathways - Erdmann, Frank; Kügler, Sebastian; Blaesse, Peter; Lange, Maren D.; Skryabin, Boris V.; Pape, Hans-Christian; Jüngling, Kay (PLOS ONE, 2015)
The neuropeptide S (NPS) system was discovered as a novel neurotransmitter system a decade ago and has since been identified as a key player in the modulation of fear and anxiety. Genetic variations of the human NPS receptor (NPSR1) have been associated with pathologies like panic disorders. However, details on the molecular fundamentals of NPSR1 activity in neurons remained elusive. We expressed NPSR1 in primary hippocampal cultures. Using single-cell calcium imaging we found that NPSR1 stimulation induced calcium mobilization from the endoplasmic reticulum via activation of IP3 and ryanodine receptors. Store-operated calcium channels were activated in a downstream process mediating entry of extracellular calcium. We provide the first detailed analysis of NPSR1 activity and the underlying intracellular pathways with respect to calcium mobilization in neurons.